Promoting Education and Employment Resources for People with Intellectual Disabilities in Ireland PEER4ID Research Report - Camedda, Donatella; Connolly, Catherine (My University, 2025)
Transitions from school into higher education and employment are important turning points in the lives of people with intellectual disabilities. These transitions can bring opportunities for learning, independence, and personal growth. However, they are often made more difficult by barriers such as fragmented systems, limited supports, and unequal access to meaningful pathways. The Promoting Education and Employment Resources for People with Intellectual Disabilities in Ireland project (referred to as PEER4ID) set out to explore these transitions in depth. The project considered both the lived experiences of people with intellectual disabilities themselves and the perspectives of those supporting them across education and employment. This approach allowed us to better understand not only the challenges but also the opportunities for creating more inclusive systems. PEER4ID was carried out in partnership with Inclusion Ireland and funded by the Irish Research Council (IRC) New Foundations Scheme 2023–2024. The Trinity Centre for People with Intellectual Disabilities (TCPID) played a pivotal role in linking the research team with the project’s civic partner. This builds on TCPID’s longstanding leadership and commitment to advancing education and employment opportunities for people with intellectual disabilities in Ireland. This report outlines the aims of the project, the research design and how it was implemented, the key findings, and the outcomes. It is presented in accessible language and with the use of visuals, so that people with intellectual disabilities can engage with the material more easily.
PUBLISHED
Keywords: Inclusive Society; Higher Education; INTELLECTUAL DISABILITY; Inclusive Education